Enhanced PI Control Based SHC-PWM Strategy for Active Power Filters - Irati Ibanez-Hidalgo; Rodrigo H. Cuzmar; Alain Sanchez-Ruiz; Angel Perez-Basante; Asier Zubizarreta; Salvador Ceballos; Ricardo P. Aguilera (IEEE Open Journal of the Industrial Electronics Society)
Low-switching frequency modulation techniques, such as selective harmonic control-pulsewidth modulation (SHC-PWM), have been recently proposed for high-power medium-voltage active power filter (APF) application. Compared to high-switching frequency modulation techniques, these methods reduce the switching losses and avoid derrating the current. This results in enhanced power density and efficiency, and facilitates a reduction in costs. However, the low-switching frequency tends to worsen the closed-loop dynamic response and system stability if countermeasures are not taken during the design process of the closed-loop controllers. Moreover, the digital filter used to obtain the harmonic components of the measured signals introduces a delay that can affect the stability and performance of the closed-loop control. This work presents different methods to improve the dynamic response of traditional proportional-integral based closed-loop controllers, which are applied along with SHC-PWM for high-power medium-voltage APFs. A current predictor that substitutes the traditional cross-coupling terms and a Smith predictor are proposed to compensate the delay introduced by the digital filters. In addition, different digital filter implementations are analyzed and compared in terms of dynamic and stationary response with the aim of improving the harmonic estimation from the measured signals. Experimental results for a 3-level NPC converter are provided to verify the effectiveness of the control.